Vacuum pulsation drying of okra (Abelmoschus esculentus L. Moench): Better retention of the quality characteristics by flat sweep frequency and pulsed ultrasound pretreatment. (1st October 2020) - Xu, Xin; Zhang, Lei; Feng, Yabin; ElGasim A. Yagoub, Abu; Sun, Yanhui; Ma, Haile; Zhou, Cunshan
Highlights: Flat sweep frequency and pulsed ultrasound (FSFPU) pretreatment improved the drying. FSFPU pretreatment reduced the vacuum pulsation (VP) drying time. The microstructure (villi and xylem) of okra pods was significantly changed. FSFPU pretreatment improved the quality characteristics of okra pods. Abstract: This study investigates the effect of flat sweep frequency and pulsed ultrasound (FSFPU) pretreatment prior to vacuum pulsation (VP) drying on water migration and quality attributes of okra pods. The results showed that the moisture diffusion was the fastest in VP drying process when FSFPU pretreatment parameters were set as 40 kHz, 25.0 W/L, sweep period 18–180 ms and amplitude ± 1 kHz. In addition, FSFPU pretreatment caused the change of microstructure (villi and xylem), resulting in significant decrease of drying time required. The VP dried okra pods with FSFPU pretreatment had features: i) increased total phenolic contents and antioxidant capacity; ii) no significant changes of total flavonoids contents; iii) a lower chlorophyll degradation (13.5% less), higher hardness and frangibility, and a lower total color change (reduced browning index); iv) reduced negative effects on the flavor. Therefore, the use of FSFPU pretreatment prior to VP drying is suggested.